2018
DOI: 10.1097/ede.0000000000000754
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Mobile Source Air Pollution in Early-life and Childhood Asthma Incidence

Abstract: Results provide limited evidence for an association of early-life mobile source air pollution with childhood asthma incidence with a steeper concentration-response relationship observed at lower levels of exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
60
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(67 citation statements)
references
References 36 publications
6
60
0
1
Order By: Relevance
“…First, we could not assess the health effects of all air pollutants because of the strong collinearity between air pollutants. Second, we only selected mortality attributed to COPD, ischaemic heart disease, stroke, and lung cancer; previous studies have shown that air pollution exposure is also associated with low birthweight and preterm birth, 39 asthma, 40 and type 2 diabetes. 41 Future studies should consider these other causes of mortality and morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…First, we could not assess the health effects of all air pollutants because of the strong collinearity between air pollutants. Second, we only selected mortality attributed to COPD, ischaemic heart disease, stroke, and lung cancer; previous studies have shown that air pollution exposure is also associated with low birthweight and preterm birth, 39 asthma, 40 and type 2 diabetes. 41 Future studies should consider these other causes of mortality and morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…The Kaiser air pollution and pediatric asthma study in the U.S. assessed over 24,000 children between the ages of 2 and 6 years. This study demonstrated that early‐life exposure to traffic‐related PM 2.5, nitric oxides, and carbon monoxide was associated with increased risk of asthma; the concentration‐response relationship being steeper at lower exposure concentrations . Ayuk et al reported a study in 10 African centers enrolled over 28,000 children aged 13 to 14 years that found an asthma prevalence of 12.8%.…”
Section: Introductionmentioning
confidence: 74%
“…Compared with dispersion models used frequently in previous studies (e.g., California Line Source Dispersion Model version 4), R‐LINE has a more advanced algorithm . The R‐LINE's model performance has been evaluated in studies by comparing the modeled PM 2.5 concentrations to the measured PM 2.5 concentrations , and it has been shown to be a valid tool in providing exposure metrics of traffic‐related air pollution in other epidemiologic studies .…”
Section: Methodsmentioning
confidence: 99%